Análise cultural do telejornalismo local: representação e identidade na RBS TV Santa Rosa - Enninger, Rossana Zott (2015)
The dissertation proposal is to conduct a cultural analysis of the Journal Lunch RBS TV Santa Rosa, station located in the northwest of Rio Grande do Sul state and whose operation began in 1992. The theoretical and methodological contributions sought up in British cultural studies and their definitions of culture as ways of life. Based on the circuit culture Paul Du Gay et al. (1999), which we use to base our methodological proposal, it becomes possible to understand the circularity of the culture that characterizes the regional television news and analyze the representation and regional identity in RBS TV Santa Rosa. Descriptive analysis we seek include instances of the production, regulation and consumption. The details of the production includes content analysis and textual analysis of each of the selected issues for this stage of the research; as regulators axes have standards that characterize the RBS TV and the Journal Lunch own; and for the analysis of consumption bring the results of research conducted with the audience of television news. In the interpretative analysis of the corpus, we stop the axes of identity and representation, understood from the speech act context reasoned through documentary sheet. For the analysis, we can say that the Journal Lunch fold the approach of a regional identity, from the recognition of a geographical proximity to information on matters disclosed to journalists who produce television news. However, the individual identities or groups which are not represented here in order to characterize the region and its 69 municipalities.